IMMU-39. NANOPARTICLE TREATMENT REBALANCES IMMUNODOMINANCE OF ANTI-VIRUS IMMUNITY TO ENHANCE ANTI-TUMOR IMMUNITY DURING ONCOLYTIC ADENOVIRUS THERAPY IN SOLID TUMORS. (14th November 2022) - Shin, Dong Ho; Jiang, Hong; Gillard, Andrew; Kim, Debora; Nguyen, Teresa; Fan, Xuejun; Yi, Yanhua; Ban, Kechen; Alemany, Ramon; Alonso, Marta M; Lang, Frederick; Gomez-Manzano, Candelaria; et al.
Abstract: Oncolytic virotherapy shows great potential for treating brain tumors and other solid tumors that metastasize to the brain. A phase I clinical trial testing the oncolytic adenovirus Delta-24-RGD (DNX-2401) in patients with recurrent malignant gliomas demonstrated significant clinical benefits for a subset of patients, and another phase I trial testing Delta-24-RGD in patients with pediatric brain tumors also indicated similar clinical benefits. However, virus injection in tumors initiates both anti-virus and anti-tumor immune responses by activating respective clones of CD8+ T-cells, which compete for limited resources for clonal expansion. Expansion of T-cells against highly immunogenic viral antigens might limit the expansion of subdominant clones against tumor antigens. We hypothesized that inducing immune tolerance for the dominant viral antigens will allow the expansion of previously subdominant tumor-specific T-cells. In this work, we observed that nanoparticles encapsulating adenoviral antigens successfully induced immune tolerance for viral antigens. These nanoparticles were taken up by liver resident macrophages, which are involved in maintaining peripheral immune tolerance. RNA-sequencing revealed that T-cells recognizing the encapsulated antigens had unique transcriptome signatures with upregulation of genes specifically involved in peripheral immune tolerance, including immune coinhibitory molecules. Virus-specific immune tolerance using nanoparticles redirected the focus of the immune response towards antigens for melanoma as measured by interferon-gamma secretion (P < 0.0001). Reduction of virus-specific T-cells and simultaneous expansion of tumor-specific T-cell clones were confirmed with tetramer staining (P < 0.05). Importantly, virotherapy in combination with nanoparticle-induced immune tolerance towards viral antigens increased the percentage of long-term survivors compared to virus treatment alone (100% versus 50%). Our data provide the basis to develop future clinical trials that aim to maximize the potential of cancer virotherapy in solid tumors.